2014
DOI: 10.5935/ambiencia.2014.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the cardinal temperatures of Purple mango cultivar through computer simulation using a nonlinear model

Abstract: A mangueira é uma espécie que se adaptou bem ao clima quente e úmido do Brasil e em especial na região do Mato Grosso. O seu crescimento e desenvolvimento está atrelado às condições ambientais em que está inserida, principalmente, a temperatura do ar, visto que esta inibe ou favorece o crescimento e desenvolvimento pela modificação das atividades enzimáticas. Alguns estudos têm utilizado dados de campo e simulação computacional como forma de avaliar as temperaturas mínima, máxima e ótima de crescimento e de de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…To enable quick and uniform emergence, budding must occur under near ideal environment conditions. CALLEJAS et al (2014) reported that the respiration, photosynthesis, growth and developmental rates are dependent on temperature. Therefore, it is vitally important to know the optimum temperature at which these processes are not adversely affected.…”
Section: Resultsmentioning
confidence: 99%
“…To enable quick and uniform emergence, budding must occur under near ideal environment conditions. CALLEJAS et al (2014) reported that the respiration, photosynthesis, growth and developmental rates are dependent on temperature. Therefore, it is vitally important to know the optimum temperature at which these processes are not adversely affected.…”
Section: Resultsmentioning
confidence: 99%
“…Cultivar Tb ( [3] Calypso 10 n/a Christmas tree 1640 adjacent Australia [2] Honey Gold 12 n/a asparagus 1800 on farm Australia [4] Honey Gold 12 n/a Christmas tree 1500 adjacent Australia [2] R2E2 12 n/a asparagus 1800 on farm Brazil [5] Tommy Atkins 13 32 Christmas tree 1428 adjacent Brazil [6] Tommy Atkins 13 32 fruit set 1158 adjacent Brazil [7] Alfa 10 n/a Christmas tree 2117 1 km from farm Brazil [8] Roxa 10.6 n/a pea size fruit 1710 n/a Brazil [9] Uba 10 n/a bud swelling 2399 n/a Mexico [10] Tommy Atkins 10 n/a Christmas tree 1600 inside canopy Mexico [10] Keitt 10 n/a Christmas tree 2100 inside canopy Mexico [10] Kent 10 n/a Christmas tree 1800 inside canopy Mexico [10] Ataulfo 10 n/a Christmas tree 1600 inside canopy India [11] Alphonso 10 n/a fruit set 1867 n/a India [11] Alphonso 17.9 n/a fruit set 919 n/a India [12] Kesar 17.9 n/a fruit set 1020 n/a References: Diczbalis et al [1], Moore [2]; Hofman et al [3]; Winston et al [4], Castro et al [5], Rodrigues et al [6], Barros et al [7], Callejas et al [8], Lemos et al [9], Osuna-Garcia [10], Zagade et al [11], Halepotara et al [12].…”
Section: Locationmentioning
confidence: 99%